A highly efficient and recyclable NiCl2(dppp)/PEG-400 system for Suzuki-Miyaura reaction of aryl chlorides with arylboronic acids. Issue 9 (3rd May 2019) - Liao, Yang; Yang, Weisen; Wei, Ting; Cai, Mingzhong
Abstract: NiCl2 (dppp) in PEG-400 is shown to be a highly efficient catalyst for Suzuki-Miyaura coupling of aryl chlorides with arylboronic acids. The reaction could be conducted at 100 °C using K3 PO4 as base, yielding a variety of biaryls in good to excellent yields. The isolation of the products was readily performed by extraction with petroleum ether and NiCl2 (dppp)/PEG-400 system could be easily recycled and reused up to five times without significant loss of activity. Our system not only avoids the use of easily volatile and toxic dioxane or toluene as a solvent but also solves the basic problem of nickel catalyst reuse. Graphical Abstract: